Clinical and economic evaluation of robotic vs. freehand screw fixation in femoral neck fractures: advancing precision alignment in orthopedics - Al-Smadi, Fawwaz; Al-Smadi, Sajeda; Xie, Xudong; Zhao, Yanzhi; Liao, Jiewen; Liu, Mengfei; Mi, Bobin; Liu, Guohui (Frontiers in Surgery, 2025)
IntroductionFemoral neck fractures are common and technically challenging injuries that often require internal fixation, with outcomes influenced by surgeon experience. This study compared clinical and economic outcomes of TiRobot-assisted vs. freehand cannulated screw fixation, focusing on alignment precision and anatomical considerations to assess the role of robotics in enhancing accuracy in orthopedic care.MethodsThis single-center retrospective cohort study included 50 adult patients with femoral neck fractures treated between July 2023 and March 2024 at Wuhan Union Hospital. Patients were followed for 12 to 20 months and evenly divided into two groups: TiRobot-assisted (n = 25) and traditional freehand fixation (n = 25). Intraoperative parameters (operative time, blood loss, fluoroscopy frequency, and screw accuracy) and postoperative outcomes (hip function, complications, hospital stay, and surgical cost) were analyzed using appropriate statistical tests.ResultsOperative time was significantly shorter in the TiRobot group (68 ± 14 min) than in the traditional group (81 ± 23.5 min; p = 0.028). Blood loss (27.68 ± 12.99 vs. 49.8 ± 15.03 mL; p < 0.001) and fluoroscopy use (12.24 ± 1.94 vs. 20.24 ± 2.47; p < 0.001) were significantly reduced. Screw parallelism was notably better in both anteroposterior (p = 0.008) and lateral views (p = 0.010). At the 12-month follow-up, Harris hip scores were higher in the TiRobot group (94 ± 8.5 vs. 87 ± 13.5; p = 0.014). Time to discharge (5.01 ± 1.46 vs. 7.03 ± 1.86 days; p < 0.001) and total hospital stay (7 ± 3 vs. 8 ± 3 days; p = 0.039) were shorter. Surgical cost was higher in the TiRobot group (CNY 28,998.31 ± 4,659.88 vs. CNY 17,653.63 ± 4,461.55; p < 0.001).ConclusionsTiRobot-assisted fixation offers greater precision, reduced intraoperative trauma, and faster recovery. Though more costly, its clinical advantages support its role in anatomically-precise orthopedic surgery.